Pragmatic Functions of Headlines in Soccer Star: A Case Study of Deictic Expression and Illocutionary Acts (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
• Adebayo, D. O., Obumneke, C. F., Ameen, A. D., & David, B. J. (2025). Language advertisement in vanguard and punch newspapers: A semantic approach. Path of Science, 11(1), 1006. https://doi.org/10.22178/pos.113-21• Agbo, I. I., & Odinakachi, O. J. (2023). Pragmatic functions of deixis in Nigerian newspaper editorials. Southern African Linguistics and Applied Language Studies, 42(1), 69–81. https://doi.org/10.2989/16073614.2023.2195885• Alkhawaldeh, A. A. (2022). Deixis in English Islamic Friday sermons: A pragma-discourse analysis. Studies in English Language and Education, 9(1), 418–437. https://doi.org/10.24815/siele.v9i1.21415• Al-Saedi, H.T.J., & Jabber, K.W. (2020). A Pragmatic Study of Newspaper Headlines in Media Discourse: Iraq as a Case Study. International Journal of Linguistics, Literature and Translation, 3, 48-59. DOI: 10.32996/ijllt.2020.3.3.6• Altun, M. (2023). The Power of Language: Exploring its Significance in Shaping Perceptions, Beliefs, and Relationships. International Journal of Social Sciences and Educational Studies, 10(3). https://doi.org/10.23918/ijsses.v10i3p362• Borchmann, S. (2024). Headlines as illocutionary subacts: The genre-specificity of headlines. Journal of Pragmatics, 220, 73–99. https://doi.org/10.1016/j.pragma.2023.12.007• Ejiaso, V.K. (2023). Actions Through Words: A Speech Act Analysis of Headline Captions of Nigerian Dailies. Nnadiebube Journal of Languages and Literatures, 1, 83-94.• Enisire, E. R. (2024). Code mixing and code switching in the popular music of Arube Otor of Isoko. Ethiope Journal of English, Literary and Cultural studies: Journal of the Department of English and Literary Studies, Delta State University, Abraka, Delta State, Nigeria, 2(1), 108-123. https://dymsb.com/index.php/EJLCSDELSU/article/view/211• Ezekulie, C.J. & Umeh, I.A. (2024). A Pragma-Stylistic Assessment of Proverbs as Speech Acts in Ifeoma Okoye's The Fourth World. Journal of English Scholars’ Association of Nigeria, 25(2), 127-142• González-Arias, C., Chatzikoumi, E., & López-García, X. (2024). The anthropomorphic pursuit of AI-generated journalistic texts: limits to expressing subjectivity. Frontiers in Communication, 9. https://doi.org/10.3389/fcomm.2024.1456509• Green, K. (2016). Deixis and Anaphora: Pragmatic Approaches. In Elsevier eBooks (pp. 415–417). https://doi.org/10.1016/b0-08-044854-2/00328-x• Grüss, H. (2025). A Critical Discourse Analysis of the Use of Person Deixis in Political Speech: Donald Trump’s strategic use of ‘Us’ and ‘Them’ Mid Sweden University Thesis. https://www.diva-portal.org/smash/get/diva2:1952439/FULLTEXT01.pdf• Jesuda, R., & Mohammed, Z. (2023). A Pragma-Stylistic Analysis of Deixis in Selected Short Stories by Kate Chopin, with Reference to Levinon's (1983) Model. ONOMÁZEIN, 62, 848-865• Kone, N. (2020). Speech Acts in UN Treaties: A Pragmatic Perspective. Open Journal of Modern Linguistics, 10, 813-827. doi: 10.4236/ojml.2020.106051.• Mabaquiao, N.M. (2018). Speech Act Theory: From Austin to Searle. A Journal for Humanities, Social Sciences, Business, and Education, 19, 35-45.• Masyhur, K., & Santoso, R. B. (2023). An Analysis of Pragmatic Deixis in Social Media. Lingua, 19(2), 169–180. https://doi.org/10.34005/lingua.v19i2.3177• Molek-Kozakowska, K. (2016). Stylistic analysis of headlines in science journalism: A case study of New Scientist. Public Understanding of Science, 26(8), 894-907. https://doi.org/10.1177/0963662516637321• Mustofa, M. (2017). Illocutionary Acts in the Headlines and Slogans of Beauty Product Advertisements. In Susana Widyastuti, Ph.D. & Paulus Kurnianta, M. Hum., English Literature Study Program. https://core.ac.uk/download/pdf/132421353.pdf• Nani, N. N. (2024). The influence of language on interaction and communication within social media platforms. Focus Journal Language Review, 2(2). https://doi.org/10.62795/fjlg.v2i2.295• Noreen, R., Bano, S., & Kanwal, T. (2025). The Pragmatic Functions of Deictic Expressions in News Headlines: A Critical Analysis. International Premier Journal of Languages & Literature, 3(2), 20-34.• Nur Setiakawanti, R., & Susanti, E. (2018). Analysis Pragmatic Study on Deixis in the Articles Jakarta Sport. Professional Journal of English Education, 1, 757-762• Nyagani, M. R., & Musa, N. (2022). Illocutionary Speech Act analysis in Nipashe newspapers’ headlines. East African Journal of Education and Social Sciences, 3(6), 24–31. https://doi.org/10.46606/eajess2022v03i06.0234• Oates, T. P., & Pauly, J. J. (2017). Sports Journalism as moral and ethical Discourse. Journal of Mass Media Ethics, 22, 332-347. https://epublications.marquette.edu/comm_fac/172• Ojo, O., & Pane, A.Y. (2024). Pragmatic Analysis of Deixis in Zikora by Chimamanda Ngozi Adichie. Veritas Journal of Humanities, 5, 24-38.• Ojomo, O. W., & Olomojobi, O. T. (2019). Viewing the game textually: online consumption of live text commentary as alternate spectatorship among Nigerian football fans. Communication & Sport, 9(3), 496–521. https://doi.org/10.1177/2167479519872721• Olagunju, S. (2016). Pragmatic Functions in 2010 World Cup Football Matches in Selected Print Media in Nigeria. Journal of Literature, Languages and Linguistics, 23, 51-56.• Olumuji, E. O. & Olufemi, O. O. (2022). Language of Reporters in Nigerian Print Newspapers. NTAtvc J of Comm., 6(2), 236 – 243.• Peterlicean, A., & Berariu, E. (2020). On the Discourse of Online Sports News Headlines. Acta Universtitatis Sapientiae. Philologica, 12(3), 155–171. https://doi.org/10.2478/ausp-2020-0029• Safi’i, N. M. (2025). Deixis in Prabowo’s Religious-Themed Speeches: A Pragmatic analysis. International Journal of English and Applied Linguistics (IJEAL), 5(1), 42–49. https://doi.org/10.47709/ijeal.v5i1.5780• Salih, S. M., & Othamn, A. R. (2024). Speech Act Theory: The Philosophical Controversy. Koya University Journal of Humanities and Social Sciences, 7(1), 532–541. https://doi.org/10.14500/kujhss.v7n1y2024.pp532-541• Selimi, F. (2024). The informativeness of headlines in daily newspapers printed in Western Balkans. In IntechOpen eBooks. https://doi.org/10.5772/intechopen.1004153• Stapleton, A., (2017). Deixis in Modern Linguistics. Essex Student Journal, 9(1). doi: https://doi.org/10.5526/esj23• Suleiman, Y., Aondover, E.M., & Abdullahi, A. M. (2023). Sports Journalism Reporting in the Era of Digital Media in Nigeria. Konfrontasi Jurnal Kultural Ekonomi dan Perubahan Sosial, 10(3). DOI:10.33258/konfrontasi2.v10i3.280• Tate, S. (2017). The professionalisation of sports journalism, 1850 to 1939, with particular reference to the career of James Catton (By University of Central Lancashire). https://core.ac.uk/download/pdf/16414685.pdf• van Hulst, M., Metze, T., Dewulf, A., de Vries, J., van Bommel, S., & van Ostaijen, M. (2024). Discourse, framing and narrative: three ways of doing critical, interpretive policy analysis. Critical Policy Studies, 1–23. https://doi.org/10.1080/19460171.2024.2326936• Vandelanotte, L. (2024). Deixis and grounding in speech and thought representation. Journal of Pragmatics, 36(3), 489–520. https://doi.org/10.1016/j.pragma.2003.10.003• Wanta, W. (2023). Reflections on communication and sport. Communication & Sport, 1(1–2), 76–87. https://doi.org/10.1177/2167479512471334• Wideyani, T., & Wulandari, A.G. (2024). Analysis of Person Deixis in the BBC Sport News Articles. Linguistics and Literature Journal, 5. DOI: https://doi.org/10.33365/llj.v5i2.5923• Wiesenborn, P. (2022). A Discourse Analysis of Cheers". Dissertations, Theses, and Projects. 735. https://red.mnstate.edu/thesis/735• Yar’Adua, N. S. M., Msughter, N. a. E., & Aliyu, N. M. A. (2023). Sports Journalism Reporting in the era of digital media in Nigeria. Konfrontasi, 10(3), 124–134. https://doi.org/10.33258/konfrontasi2.v10i3.280